Hybrid UHF/UWB antenna for passive indoor identification and localization systems - Cruz, C. C.; Costa, J. R.; C. A. Fernandes (IEEE Transactions on Antennas and Propagation, 2013)
There is a growing interest for simultaneous identification and centimetre-resolution localization of multiple targets in indoor environments. A hybrid passive UHF/UWB RFID concept has been recently proposed that conciliates the potential from high resolution UWB impulse radio with the typical range from UHF-RFID identification systems. This paper proposes a new planar antenna for hybrid passive tag systems, which operates both in the UHF-RFID band and in the FCC UWB band. The co-designed UHF and UWB antenna elements are printed back-to-back on each side of a common substrate with appropriate topology for future integration with a single UHF-UWB RFID chip. Experimental tests have shown that both UHF-RFID and UWB performance of the hybrid antenna are comparable to available commercial solutions that work just on a single band. The antenna is adequate for low-cost mass production of hybrid passive tags. It aims at low-cost passive RFID systems combining the ability of item identification with precise tracking in indoor environments.